The Effect of Dollar Exchange Rate of The Finance Performance in Indonesia: The Effect of Dollar Exchange - Adil, Siswanto; Irfan Fatoni, Muhammad; Kakati, Shivam (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2024)
There was an increase of more than 1.57 million Single Investor Identification or 21% from the previous year amidst economic stagnation during the Covid-19 pandemic and a recession projected in 2023 by the Ministry of Finance which was caused by the weakening of two sectors (food and finance). This second factor is the background for researchers to determine the influence of the exchange rate, inflation and Gross Development Product on the performance of financial sector stocks in 2015 to 2022. The results of several previous studies, there are inconsistent and require further researches. Based on the results of previous research in the financial sector with the underlying theory, it shows that there are still gaps or inconsistencies of research results as well as economic instability after the Covid-19 pandemic in 2020. Further research is needed which aims to find out how the exchange rate is affected, Inflation and Gross Development Product of the finance performance sector share. This research is quantitative using multiple linear regression analysis with a descriptive approach. The data used is secondary obtained from the official websites of Indonesian Bank, Central Statistics Agency, and Central Statistics Agency, as well as the Stock Exchange Investment Gallery.